Pengembangan Desain Pendidikan Karakter Berbasis Pembiasaan Sholat Dhuha Berjamaah di Sekolah Menengah Kejuruan: The Development of Character Education Design Based on the Habit of Congregational Dhuha Prayer in Vocational High School - M. Fajar Febrian; Abdul Latif; Abi Walid; Sita Acetylena (STAI Ma'had Aly Al-Hikam Malang, 2026)
This research aims to formulate a character education model built through the habituation of congregational Dhuha prayer at SMK Turen in 2025, serving as a strategy to strengthen students' religious character and discipline. The approach applied is Research and Development (R&D) using the ADDIE model, which encompasses the stages of analysis, design, development, implementation, and evaluation. Data collection was conducted through observation, interviews, questionnaires, and documentation studies, and subsequently analyzed using qualitative and quantitative methods. The research findings reveal that the resulting design integrates religious values into learning activities, designs schedules and procedures for congregational Dhuha prayer, and develops habituation monitoring instruments. Expert validation results categorized the design as